Agri-food 4.0 : innovations, challenges and strategies - Mohr, Rahul S.; Kumar, Dinesh; Singh, Anupama (Emerald Publishing Limited, 2022)
The Agri-Food industry currently faces a range of challenges, from food safety and security, demand, and supply gaps to the maintenance of product quality and issues in product traceability. Smart digital technologies have opened a complete paradigm shift, providing solutions to these challenges, and helping move towards safe, resilient, responsive, and eventually profit-driven supply chains. The use of these digital technologies by Agri-Food supply chains can bring significant changes in food supply chain management by reducing food wastage, real-time product monitoring, and reducing scalability issues. Agri-Food 4.0: Innovations, Challenges and Strategies addresses new research on digital technologies in the industry, including smart packaging, smart warehousing, effective inventory control, blockchain technology, artificial intelligence, and other Industry 4.0 concepts. Agri-Food 4.0 explores the challenges and complexities in implementing such technologies, helping policymakers in the agri-food sector with impact assessment and digital transformation towards creating a sustainable industry.
Includes index.
Keywords: Agricultural processing industries.; Industry 4.0.; Business & Economics -- Industries / Agribusiness.; Agriculture & related industries.; elektronické knihy; electronic books